2002
DOI: 10.1038/oby.2002.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Energy Expenditure and Ucp1 on Photoperiod‐Induced Weight Gain in Collared Lemmings

Abstract: POWELL, CHARLES STEPHENSON, MATTHEW L.BLAYLOCK, RUIXUE WANG, HEATHER L. HUNTER, GARY L. JOHANNING, AND TIM R. NAGY. Effects of energy expenditure and Ucp1 on photoperiod-induced weight gain in collared lemmings. Obes Res. 2002;10: 541-550. Objective: To determine the role of total energy expenditure (TEE) and its components in the ability of collared lemmings to increase weight in response to a decrease in photoperiod. Research Methods and Procedures: Energy expenditure was measured by 24-hour indirect calori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 31 publications
3
24
1
1
Order By: Relevance
“…Our data show that during this phase food intake levels remain unchanged, strongly implicating changes in expenditure (either RMR or physical activity) as the mechanism used to increase body mass. Recent studies of collared lemmings (Dicrostonyx groenlandicus) suggest that reductions in RMR facilitate mass gains after photoperiod changes (Powell et al, 2002), consistent with the absence of differences in food intake during this phase in our study. Our future work will focus on this dynamic phase to elucidate in more detail the whole-body energy balance and central signalling mechanisms that underpin the body mass increase.…”
Section: Hypothalamic Neuropeptide and Receptor Gene Expressionsupporting
confidence: 77%
“…Our data show that during this phase food intake levels remain unchanged, strongly implicating changes in expenditure (either RMR or physical activity) as the mechanism used to increase body mass. Recent studies of collared lemmings (Dicrostonyx groenlandicus) suggest that reductions in RMR facilitate mass gains after photoperiod changes (Powell et al, 2002), consistent with the absence of differences in food intake during this phase in our study. Our future work will focus on this dynamic phase to elucidate in more detail the whole-body energy balance and central signalling mechanisms that underpin the body mass increase.…”
Section: Hypothalamic Neuropeptide and Receptor Gene Expressionsupporting
confidence: 77%
“…In adults of most rodent species, SD enhances UCP1 content in BAT as reported for common spiny mice (Acomys cahirinus) (Kronfeld-Schor et al, 2000), Siberian hamsters ) and Brandt's voles (Zhao and Wang, 2005). In the present study, the response to postweaning photoperiod was similar to that described in the abovementioned results but opposite to the SD-induced declines in UCP1 mRNA level and resting energy expenditure in collared lemmings (Powell et al, 2002). Of particular interest in our study was that we found evidence that SD both before and after weaning significantly increased UCP1 content; SS voles had the highest content of all groups (Fig.·5).…”
Section: Effects Of Photoperiod History On Thermogenic Capacitysupporting
confidence: 76%
“…Studies concerning the effects on energy expenditure of photoperiod history have been conducted predominantly in adult animals. Powell et al (Powell et al, 2002) found that when long photoperiod (LD) collared lemmings (Dicrostonyx groenlandicus) were exposed to a short photoperiod (SD), resting energy expenditure and uncoupling protein 1 (UCP1) mRNA levels in brown adipose tissue (BAT) decreased. In some species such as Siberian hamsters (Phodopus sungorus), SD acclimation increased non-shivering thermogenesis (NST) and UCP1 content .…”
Section: Introductionmentioning
confidence: 99%
“…Syrian hamsters housed in groups for 65-75·days displayed a chronic 13% reduction in massspecific resting metabolic rate, accompanied by a 20% increase in body mass and a 53% increase in body fatness, relative to individuals housed individually (Borer et al, 1988). Decrease in maintenance metabolism has also been demonstrated in collared lemmings (Powell et al, 2002). In particular, male lemmings exposed to SD for 10·days had significantly lower total energy expenditure, resting energy expenditure and UCP-1 mRNA levels than animals maintained in LD, whereas nonresting energy expenditure (related to activity) was not affected by photoperiod.…”
Section: Discussionmentioning
confidence: 78%